Characterization of light-induced potentials in the strong-field dissociation of O2+ - Abanador, P. M.; Thumm, U. (My University, 2020)
We investigate theoretically the imprints of light-induced potentials (LIPs) on the dissociation dynamics of O2+ molecular ions, as observable in angle-resolved fragment kinetic-energy-release (KER) spectra. Following the vibrational and rotational dynamics of the initial pump-laser-excited cationic nuclear wave packet, while accounting for the dipole coupling between the O2+(a4Πu) and O2+(f4Πg) electronic states in 800-nm 40-fs probe-laser pulses with peak intensities between 1013 and 1014 W/cm2, we calculate angle-resolved KER spectra which reveal characteristic energy- and angle-dependent fringe structures. These fringes shift downward in energy as the molecular alignment angle θ relative to the probe-pulse polarization direction increases from 0 to π/2. The angle-dependent shifts in the KER fringes increase for larger probe-pulse peak intensities and follow the angle and light-wave-intensity dependence of the vibrational spectrum in the associated Floquet bond-hardening well, which is a manifestation of transient O2+ nuclear-probability trapping in the LIP during dissociation. By examining the rovibrational dynamics of the dissociating molecular cation near the light-induced conical intersection (LICI) in the cationic LIP surface at θ=π/2, we identify related angle-dependent structures in the KER spectra, suggesting a means for assessing the significance of LICIs in molecular dissociation pathways.